2016
DOI: 10.1016/j.molcel.2016.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MicroRNA Levels, Target-Site Complementarity, and Cooperativity on Competing Endogenous RNA-Regulated Gene Expression

Abstract: SummaryExpression changes of competing endogenous RNAs (ceRNAs) have been proposed to influence microRNA (miRNA) activity and thereby regulate other transcripts containing miRNA-binding sites. Here, we find that although miRNA levels define the extent of repression, they have little effect on the magnitude of the ceRNA expression change required to observe derepression. Canonical 6-nt sites, which typically mediate modest repression, can nonetheless compete for miRNA binding, with potency ∼20% of that observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
276
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(284 citation statements)
references
References 37 publications
8
276
0
Order By: Relevance
“…Our observation of Tmsb4x-mediated titration is thus consistent with the conclusions of Bosson et al (2014). It is, however, hard to reconcile with the notion proposed by Denzler et al (2016), stating that an efficient titrating site has to reach ∼10%-40% of the effective target abundance, which can be roughly estimated by the total concentration of 6-, 7-, and 8-mer 3 ′ UTR sites for the miRNA of interest. In our libraries, the Tmsb4x miR-1a/miR-206 binding site accounts for ∼1% of the total miR-1a/miR-206 3 ′ UTR sites.…”
Section: Wwwgenomeorgsupporting
confidence: 86%
See 2 more Smart Citations
“…Our observation of Tmsb4x-mediated titration is thus consistent with the conclusions of Bosson et al (2014). It is, however, hard to reconcile with the notion proposed by Denzler et al (2016), stating that an efficient titrating site has to reach ∼10%-40% of the effective target abundance, which can be roughly estimated by the total concentration of 6-, 7-, and 8-mer 3 ′ UTR sites for the miRNA of interest. In our libraries, the Tmsb4x miR-1a/miR-206 binding site accounts for ∼1% of the total miR-1a/miR-206 3 ′ UTR sites.…”
Section: Wwwgenomeorgsupporting
confidence: 86%
“…It has been proposed that efficient titration could be restricted to high-affinity target sites, for miRNAs with a low miRNA:target ratio (Bosson et al 2014). But another study, performed on a similar biological system with a different methodology, concluded that even poorly expressed miRNAs are unlikely to be efficiently titrated by any individual mRNA (Denzler et al 2016).…”
Section: Assessement Of Mirna Titration By Mrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, and as we show here, GW182 preference toward guide-RNA loaded Argonautes (Figures 1D and 1E) ensures that only guide-primed Argonautes will be recruited by GW182 where RISC is most likely already assembled on its target mRNA (Wee et al, 2012). This GW182 mediated interaction of the RISC with multiple adjacent sites on the same transcript can result in longer dwelling on the target transcript as was suggested recently (Denzler et al, 2016). …”
Section: Discussionsupporting
confidence: 58%
“…In that mechanism, a noncoding RNA containing a sequence motif that is complementary to a miRNA sequesters the respective miRISC and thus renders it unavailable for inhibition of regular mRNA targets (Franco-Zorrilla et al, 2007). In animals, competing endogenous RNAs play a similar role, although their biological significance remains controversial (Bak and Mikkelsen, 2014;Wang et al, 2015;Denzler et al, 2016). Only a single case of natural miRNA target mimicry, that of INDUCED BY PHOSPHATE STARVATION1 (IPS1), which interferes with the activity of miR399, has been studied in detail in plants (Franco-Zorrilla et al, 2007).…”
mentioning
confidence: 99%